Association between childhood negative life events with alcohol expectancies in early adolescence: Cumulative risk and latent class approaches. (1st September 2021) - Chen, An-Jou; Chen, Wan-Ting; Wang, I-An; Wang, Nadia; Chen, Wei J.; Chen, Chuan-Yu
Highlights: Childhood NLEs can be characterized by three distinct classes: "lesser experience, " "family instability, " and "stressed relationship. Experiencing multiple or "stressed relationship" class NLE may significantly increase endorsed overall AEs. NLEs-related increase in AE was especially prominent in the domains regarding "promoting relaxation or tension reduction" and "global transformation". Abstract: Background: The present study aims to investigate the effects of childhood negative life events (NLEs) on alcohol expectancies (AEs) in early adolescence through cumulative risk and latent class approaches. Methods: Data were obtained from a prospective cohort of 945 sixth graders (age 11–12) ascertained from 17 elementary schools in northern Taiwan (response rate = 61.0 %wt ); subsequent assessments were conducted during eighth grade (n = 775, follow-up rate [FR] = 82.6 %wt ). Information concerning socio-demographics, 14 NLEs, alcohol-related experience, and four-domain AEs was collected by self-administered questionnaires at childhood and follow-up. Latent class and multivariate analyses were used to evaluate the association estimates. Results: Nearly one half of children had experienced at least one NLE in sixth grade, with one-tenth experiencing four or more NLEs. Three latent classes of NLEs were identified: "lesser experience (68.1 %wt ), " "stressed relationship (27.6 %wt ), " and "family instability (4.3 %wt )." The observed NLE-associated increase in AEs was relatively stronger in the cumulative approach: children experiencing four or more NLEs (βwt = 1.27, 95 % CI = 0.27–2.27) and in the "stressed relationship" NLE class appeared to develop greater AEs (βwt = 0.86, 95 % CI = 0.30–1.42). Moreover, such NLE-associated increase was especially salient in the AE domains regarding "global positive transformation" and "promoting relaxation or tension reduction". Conclusions: Our results provide insight into which experiences of multiple and "stressed relationship" negative life events arising from the family context in childhood may shape endorsed alcohol expectancies in adolescence, and implied that such effects may not uniformly operate across AE domain.